Effectiveness of Humanistic Approach Assisted by Learning Media to Increase Motivation Student Learning in MTs Darul Huffaz Pesawaran - Hernadi Hernadi; Rangga Firdaus; Nurlaksona Eko Rusmianto (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Learning motivation is an absolute requirement for learning and plays an important role in providing passion or enthusiasm in learning. Motivation to learn is not only a driving force to achieve good results but contains efforts to achieve learning goals in motivation contained a desire that activates, moves, channels and directs attitudes and behavior in individuals. The humanistic approach views humans as subjects who are free to determine the direction of their lives. Humans are responsible for their own lives and for the lives of others. This research aims to explain the humanistic approach assisted by learning media to increase students' learning motivation.This research uses the (SLR) method. regarding research methods: "Literature" which means it is a critical analysis of the research that is being carried out on a special topic or in the form of a question to a part of science. helps us in compiling a framework that is in accordance with the theory, findings, and results of previous research in solving the problem formulation in the research conducted. The results of the study described that, of course, learning motivation must be supported by anyone who provides teaching to students, especially by teachers as learning facilitators, through humanistic approaches the teacher will know and understand the characteristics of students who experience decreased interest in learning, the humanistic approach is designed to solve problems that arise from within a person with a humanistic approach, of course someone will carry out treatment by humanizing humans by humanizing the problems that occur, especially in the learning and learning process